Algunas precisiones respecto a los vehículos societarios y los conflictos de interpretación que enfrentamos hoy en día - Pérez León, Martín Serkovic (2020)
Throughout the following article, the author addresses the main concepts regarding figures related to business engagement, referencing also those concepts addressed in both legal doctrine and business practices. Since companies can be linked in many ways, it is necessary to draw the main differences between them in order to avoid interpretation errors, on the basis that each corporate figure implicates its own regulation. The so-called “corporate control” will also be analyzed in order to determine how to address the interpretation errors found in current practices.